Pendampingan Kompetensi Guru SMP Tahfidzul Qur’an melalui Program In-House Training (IHT) dalam Penyusunan Silabus dan Perangkat Pembelajaran - Muhammad Syarofi (Institut Agama Islam Insan Prima Misbahul Ulum Gumawang, 2025)
The low level of pedagogical competence and the limited ability of teachers at SMP Tahfidzul Qur’an Paleran to design innovative, contextual, and Qur’an-based learning devices highlight the urgent need to enhance teachers’ professional capacity through practical training aligned with the Merdeka Curriculum. The In-House Training (IHT) program was implemented as a strategic effort to strengthen teachers’ pedagogical understanding, technological integration skills, and the development of learning tools relevant to students’ characteristics and Islamic educational values. This training aimed to equip teachers with practical skills in designing differentiated lesson plans (RPP), integrating simple digital technologies, and developing interactive learning media that support 21st-century learning. The program adopted a participatory and product-oriented approach, conducted at SMP Tahfidzul Qur’an Paleran, Jember. The activities consisted of three main stages: preparation, implementation through thematic workshops, and formative evaluation using observation, pre-test, and post-test instruments. The results showed a significant improvement in teachers’ understanding of innovative learning design, digital media utilization, and the application of project- and problem-based learning models. Approximately 90% of participants actively engaged in discussions and successfully produced lesson plans and digital media aligned with Higher Order Thinking Skills (HOTS) indicators. The program also fostered professional collaboration and reflective practice among teachers. It is recommended that continuous mentoring be provided through professional learning communities and the development of IHT models integrating Islamic values and educational technology to enhance teachers’ adaptability to digital transformation in education.